A study of low-cost adsorbent materials for removing cr(vi) from aqueous waste effluent (2011)
The present paper shows very high potential for two types of solid (a commercial alumina and material obtained by composting, i.e. matured compost) on Cr(VI) adsorption/elimination in aqueous solution using a concentration range close to those previously detected in waste-water from Colombian industries. Both had important properties for eliminating Cr(VI), the compost being more important as it represents low-cost material. Optimal conditions for chromium adsorption on alumina and compost were established. Initial Cr(VI) alumina concentration was 10 mgL-1, with 100 mL/g volume of solution per adsorbent mass, pH=2.0, 1 hour equilibrium time and 150 rpm stirring. For compost, initial Cr(VI) concentration was = 3 mg L-1, 50 mL/g volume of solution per adsorbent mass, pH=2.5, 3 hour equilibrium time and 150 rpm stirring. The experiments showed that compost adsorption properties could be enhanced by adding small quantities of alumina. Compost could thus be chosen as a promising material for use in bioremediation chromium-containing waste water in a management programme for using solid waste in for minimising environmental impact.